Madness and Social Change Autobiography of the Brazilian Psychiatric Reform - Amarante, Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
In this book, the history of the Brazilian Psychiatric Reform is told by one of its main protagonists. In the early 1980s, there were about 80 thousand people admitted to psychiatric hospitals in Brazil, with average lengths of hospital stay of approximately 25 years. The psychiatric reform process that took place in the country was responsible for closing more than 60 thousand beds in mental asylums, most of them characterized by conditions of violence and abandonment. The Brazilian Psychiatric Reform was inspired by the psychosocial care model introduced by psychiatrist Franco Basaglia in Italy and was marked by the broad participation of social movements, such as the anti-asylum movement and other human rights movements. This process gave rise to a model of mental health care based on open-door territorial mental health services, guided by the principle of treatment in liberty, in addition to other strategies of deinstitutionalization. More than a proposal to restructure or modernize the mental health care model, the objective of the Brazilian Psychiatric Reform was the construction of a new social place for the diverse and singular subjective experience of madness. By intending to produce new imaginaries, new social representations and new meanings for these experiences, the Brazilian Psychiatric Reform led to one of the larger experiences of deinstitutionalization in the world and to the large scale implementation of a new model of mental health care in which the old asylum-centric paradigm was replaced by a new democratic psychosocial care model. .
1. Introduction: Dimensions of the Psychiatric Reform as a complex social process -- 2. The "Industry of Madness" is denounced! The birth of the Brazilian Psychiatric Reform -- 3. The sociocultural dimension: Concrete experiences of production of a new social place for madness and psychological suffering -- 4. Final considerations and comments: Health and psychiatric counter-reform or dismantling the rule of law in Brazil?.
Keywords: Public health; Mental health; Medical policy; Psychiatry; Public Health; Mental Health; Health Policy; Psychiatry; Mental Health Services; Brazil